Obesity and glomerular filtration rate (2023)
Obesity has received considerable attention in general medicine and nephrology over the last few years. This condition increases the risk of metabolic syndrome, diabetes mellitus, hypertension, and dyslipidemia, which are the main risk factors for developing chronic kidney disease (CKD). Kidney damage caused by obesity can be explained by many mechanisms, such as sympathetic nervous and renin-angiotensin-aldosterone systems activation, mechanical stress, hormonal unbalance, as well as inflammatory cytokines production. Even though creatinine-based glomerular filtration rate (GFR) equations in obese individuals have been validated (Salazar-Corcoran and CKD-MCQ), changes in body weight after bariatric surgery (BS) leads to changes in creatininemia, affecting its reliability. Thus, an average between creatine and cystatin-based GFR equations would be more appropriate in this setting. Bariatric surgery can reverse diabetes mellitus and improve hypertension, which are the main causes of CKD. Conclusion: GFR can be affected by obesity and BS, and its value should be cautiously evaluated in this setting.